Sensory Marketing Strategies and Their Influence on Purchasing Decisions in Offline Retail - Nasaruddin Nasaruddin; Andi Wahyuni Syam; Anugrahwati Anugrahwati; Ana Andania; Ismail Ismail (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study examines the role of sensory marketing strategies in enhancing shopping experiences and consumer loyalty in offline retail in the semi-urban area of Bone Regency. Using a qualitative approach with in-depth interviews and participatory observation, this study found that sensory elements such as lighting, music, aroma, and opportunities for direct interaction with products significantly influence consumer comfort, positive emotions, and visit duration in stores. The optimal implementation of sensory strategies increases the likelihood of impulse purchases and builds positive perceptions, satisfaction, and customer loyalty. These findings confirm that physical stores retain a unique advantage as a multisensory experience arena that digital channels cannot fully replace. However, the study also identified challenges such as resource constraints, varying consumer preferences, the need for more personalized service, and innovation in promotions and store facilities. The practical implications of this research encourage retailers to be more structured in designing store ambience, enhancing staff training, and integrating experience-based loyalty programs. Further research is recommended to expand the context, quantitatively measure the specific contributions of each sensory element, and explore the integration of sensory strategies with digital innovations within an omnichannel ecosystem.